A DISCOURSE OF SHARIA BANKING SUPERVISION MODELS IN ACEH - Munawar Rizki Jailani (IAIN Lhokseumawe, 2022)
The Helsinki MoU gave Aceh the privilege to regulate the banking sector independently. Then the Qanun of Islamic Financial Institutions (LKS) instructed Aceh to have a single banking system, meaning that Aceh only knows Islamic banking. One of the characteristics of Islamic banking is sharia supervision. The purpose of this article is to discuss the banking sharia supervisory model in Aceh. The method used in this study is qualitative with a descriptive approach, documents published and not compiled are then classified into several segments which are then analyzed both deductively and inductively. The study results show that Aceh's specificity through the Helsinki MoU and the implementation of the LKS Qanun has not been seen in the banking sharia supervision there. Banking sharia supervision is still carried out by the Financial Services Authority (OJK) and the National Sharia Council (DSN). The formation of the Aceh Sharia Council has not delivered any meaning in banking supervision in Aceh. Therefore the authors provide three alternatives so that banking sharia supervision in Aceh is by the Helsinki MoU and the LKS Qanun.